2021
DOI: 10.1177/0004867421998770
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of women with borderline personality pathology referred to a perinatal consultation liaison service

Abstract: Objective: To examine the prevalence and characteristics of pregnant women with borderline personality pathology (defined as borderline personality disorder and borderline personality traits) referred to a perinatal consultation-liaison psychiatry service. Method: Socio-demographic and clinical data, and diagnoses made according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria were recorded for all women referred to and seen by the perinatal consultation-liaison psychiatry service ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This included current use of alcohol and/or drugs, and frequent high risk to life behaviours such as “cutting, overdosing or endangering life including excess use of alcohol and/or non-prescribed medication”. Given BPD/trauma is frequently characterised by substance use and self-harm (Dunn et al, 2020 ; Nagel et al, 2021 ; Sved Williams & Apter, 2017 ), sample representativeness and consequently outcomes may be questionable. It is additionally noted that some BPD/trauma behaviours are incompatible with eastern and collectivist societies, for example substance use and promiscuous sex in China (Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This included current use of alcohol and/or drugs, and frequent high risk to life behaviours such as “cutting, overdosing or endangering life including excess use of alcohol and/or non-prescribed medication”. Given BPD/trauma is frequently characterised by substance use and self-harm (Dunn et al, 2020 ; Nagel et al, 2021 ; Sved Williams & Apter, 2017 ), sample representativeness and consequently outcomes may be questionable. It is additionally noted that some BPD/trauma behaviours are incompatible with eastern and collectivist societies, for example substance use and promiscuous sex in China (Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…BPD is also a disorder that commonly affects women of reproductive age, with presentations often occurring in the perinatal setting with potential downstream consequences on the development of their offspring. Prasad et al 5 found the pooled prevalence of BPD in perinatal women to be 14% while Nagel et al 6 in their study at a tertiary maternity hospital found 10.1% met BPD criteria while 19.5% had BPD traits. To the best of our knowledge there have been only four studies examining the obstetric, neonatal, and social outcomes for pregnant women with BPD.…”
mentioning
confidence: 96%
“…The studied population also displayed high rates of substance abuse and child protection involvement. Another study by Nagel et al 6 found that when compared to unmatched controls, pregnant women who met the clinical criteria for BPD and those with subthreshold BPD traits had high rates of unplanned pregnancy, being unpartnered, having substance use, and child protection involvement during pregnancy. This study also highlighted the diagnostic challenge of BPD in the perinatal period with psychiatric comorbidity being common.…”
mentioning
confidence: 99%